Experimental measurement and modelling of surface roughness in turning with CaF2 solid lubricant assisted minimum quantity lubrication. (2019) - Makhesana, Mayurkumar A.; Patel, Kaushik M.
To improve the quality of a product, it is important to evaluate, both experimentally and analytically, the factors affecting the machining process. In this context, the proposed work focuses on the modelling and analysis of surface roughness measured in a turning process with wet and minimum quantity solid lubrication (MQSL) approaches. In the MQSL application, micron-sized calcium fluoride (CaF2 ) solid lubricant powder particles are mixed in Society of Automotive Engineers (SAE) 40 cutting oil and applied to a machining zone. It also provides a predictive model for the minimisation of the surface roughness in turning operations in wet and MQSL environments. The correlation between the cutting parameters and measured surface roughness in wet and solid lubricant assisted machining is determined. Results indicate that surface roughness is affected by feed, depth of cut followed by cutting speed. These outcomes can be used by the machining industry to use the best combination of parameters affecting surface roughness with the MQSL approach.